TOWARD PERSONALIZED MAGNETIC RESONANCE GUIDED FOCUSED ULTRASOUND THALAMOTOMY FOR ESSENTIAL TREMOR: PATIENT-RELATED PREDICTORS OF TREATMENT OUTCOME - Ananda, Naoval Diza; Nugraha, Priya; Izzah, Alfira Nailatul (MNJ (Malang Neurology Journal), 2026)
Background: Magnetic resonance-guided focused ultrasound (MRgFUS) thalamotomy is a minimally invasive alternative for essential tremor (ET). However, treatment response varies across patients, and identifying patient-related predictors of outcome is crucial to guide selection and optimize results. Objective: This review summarizes recent evidence of patient-related predictors that correlate with treatment outcomes of MRgFUS thalamotomy in patients with ET. Methods: We conducted a systematic review of PubMed, Scopus, and ScienceDirect from January 2010 to August 2025 based on the Preferred Reporting Items for Systematic Reviews and Analysis (PRISMA) guidelines. Results: Thirteen studies involving 1,169 participants with mean age of 70.9 ± 10.4 years were included. Five out of nine (55.5%) studies reported significance of age in treatment outcomes. Two out of nine (22.2%) studies reported significance of skull density rate (SDR) in treatment outcomes. Out of four studies reported baseline clinical rating scale of tremor (CRST) score, all of them (100%) reported significance in treatment outcomes. Two out of four (50%) studies reported significance of duration of illness in treatment outcome. One study evaluated quality of life and found no significant patient-related outcome predictors. Conclusion: Patient-related predictors including age, skull density ratio, baseline CRST score, and disease duration appear to influence MRgFUS outcomes in patients with ET. Incorporating these factors into patient selection may improve treatment success. Further research is required to establish cutoff values and explore additional predictors.